2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259352
|View full text |Cite
|
Sign up to set email alerts
|

New Methodology For Preventing Pressure Ulcers Using Actimetry and Autonomous Nervous System Recording

Abstract: Pressure ulcers constitute an important health problem. They affect lots of people with mobility disorder and they are difficult to detect and prevent because the damage begins on the muscle. This paper proposes a new approach to study pressure ulcers. We aim at developing a methodology to analyse the probability for a patient to develop a pressure ulcer, and that can detect risky situation. The idea is to relate the mobility disorder to autonomic nervous system (ANS) trouble. More precisely, the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…60,61,69 Bioimpedance spectrometers were proposed to identify the variations of complex electrical impedances consequent to pathological changes in the skin or underlying deep tissues. 71,72 Instruments that measure the frequency-dependent viscoelastic response of soft tissues are also being tested. The actimeter records the movement of the skin surface in contact with the underlying surface, whereas the recorded autonomic nervous system activity level represents the degree of patient discomfort.…”
Section: Recent Technological Advances In Screening Methods For Stagementioning
confidence: 99%
“…60,61,69 Bioimpedance spectrometers were proposed to identify the variations of complex electrical impedances consequent to pathological changes in the skin or underlying deep tissues. 71,72 Instruments that measure the frequency-dependent viscoelastic response of soft tissues are also being tested. The actimeter records the movement of the skin surface in contact with the underlying surface, whereas the recorded autonomic nervous system activity level represents the degree of patient discomfort.…”
Section: Recent Technological Advances In Screening Methods For Stagementioning
confidence: 99%
“…The E.motion device records: skin potential, skin resistance, skin temperature, skin blood rate, instantaneous cardiac frequency and instantaneous respiratory frequency. The complete study is reported in [6]. Actually, actimetry is only related to the Heart Rate Variability (HRV).…”
Section: A Methodsmentioning
confidence: 99%
“…A new actimeter system has been designed in order to study movements of the human body whatever its support while seating [6]. This evaluation, at the interface between soft living tissues and any support has to consider the specificity of the human environment.…”
Section: ) Ambulatory Device For Pressure Ulcer Preventionmentioning
confidence: 99%